Self-Mapping in Counselling: Using Memetic Maps to Enhance Client Reflectivity and Therapeutic Efficacy - Robertson, Lloyd Hawkeye (Canadian Journal of Counselling and Psychotherapy, 2016)
Combining theory and practice, this article demonstrates how the construct of the self may be represented graphically with implications for our understanding of self-determination and counselling. It begins with a review of attempted graphic self-representations in psychology, social work, and education. The self is then situated ontologically within the perspective of cultural evolution, and this paradigm is used to inform the construction of maps consisting of units of culture called memes. Graphic self-maps of two individuals, one in counselling and one not, are compared and contrasted. The self-maps depict self-defining cognitive structures combined with psychological and environmental determinants. It is proposed that such graphic illustrations could benefit counsellors and their clients in planning and executing transformative change. Further research is recommended that explores the effect of self-mapping on client empowerment, the structure of client selves, and the use of mapped cognitive pathways in treatment.